2018
DOI: 10.1038/s42003-018-0156-x
|View full text |Cite
|
Sign up to set email alerts
|

2D polarization imaging as a low-cost fluorescence method to detect α-synuclein aggregation ex vivo in models of Parkinson’s disease

Abstract: A hallmark of Parkinson’s disease is the formation of large protein-rich aggregates in neurons, where α-synuclein is the most abundant protein. A standard approach to visualize aggregation is to fluorescently label the proteins of interest. Then, highly fluorescent regions are assumed to contain aggregated proteins. However, fluorescence brightness alone cannot discriminate micrometer-sized regions with high expression of non-aggregated proteins from regions where the proteins are aggregated on the molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Such energy migration events between the different randomly oriented identical fluorophores positioned within the Förster distance depolarize the fluorescence anisotropy because of the apparent orientational randomization independent of rotational dynamics. Such a depolarization via homo-FRET has been previously observed in a-syn amyloid fibrils (30)(31)(32). The energy migration efficiency measured by the observed loss in the fluorescence anisotropy at a given local density of fluorophore is related to the interdye distance.…”
supporting
confidence: 53%
“…Such energy migration events between the different randomly oriented identical fluorophores positioned within the Förster distance depolarize the fluorescence anisotropy because of the apparent orientational randomization independent of rotational dynamics. Such a depolarization via homo-FRET has been previously observed in a-syn amyloid fibrils (30)(31)(32). The energy migration efficiency measured by the observed loss in the fluorescence anisotropy at a given local density of fluorophore is related to the interdye distance.…”
supporting
confidence: 53%
“…We have shown that including the polarization degree of freedom in the localization analysis allows for more robust assignment of fluorescence photons to individual emitters. Aside from boosting the localization accuracy, this approach also provides direct access to molecular orientations which can be useful in the context of studying agglomeration or oligomerization of proteins. Furthermore, we have shown that polarization can be used to achieve controllable switching, which is largely independent of the stochastic blinking, works with lower light levels and allows for longer camera integration times. The implementations of the ideas in our work are straightforward and not restricted to specific photophysical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of co-diffusion suggests that this complex is not strongly fluorescent (e.g., due to self-quenching) but still primarily recognized by the Nb. Fluorescence modulation upon aggregation or mis-folding of FPs and their chromophores has been described before (Camacho et al, 2018;Ge et al, 2017;Jung et al, 2005b;Kruitwagen et al, 2015;Stepanenko et al, 2008). Upon binding, Nb could partially disassemble the dark complex and release a few molecules from the complex that become fluorescent but are not bound to a Nb.…”
Section: Discussionmentioning
confidence: 81%